VVU bibliotekininkystės ir mokslinės informacijos katedros absolventai Lietuvos TSR bibliotekose - Dirgėlaitė, Bronė (Knygotyra, 1976)
The Library Science and Scientifical Information Chair of the Historical faculty of the Vilnius V. Kapsukas State University is the only college in Lithuania giving the high education to the librarians. The Chair began the 1972–1973 year with celebrating its twentieth anniversary. During a short period the Chair achieved good results in various branches. It gave scilled specialists for the libraries of our republic and develops the scientific and resurch activity e. t. c. But the main task of the Chair is to give practical and theoretical knowledge to the young specialists.Having shown some not well known facts about the contingent of the specialists educated at the Chair and their dislocation, the author of the article makes an attempt to find the place and the role of the graduates in the library life of our republic. Wheu speaking about the distribution the author of the article speaks only about the day students. It is quite impossible to Collect the punctual facts about the correspondent students. When collecting the information about the day students we have possibility to note where the greduates work at the present time as well as to learn the facts of their distribution.The whole material of the article about the contingent of the abiturients and the graduates and the facts about the distribution of the young specialists was taken from the Studying Departament and the Central Archives of Vilnius State University. The graduates of the Chair themselves lave sent much information about the places of their work. The whole material and the figures are represented by the means of tables, made by the author of the article.All what we know shows, that the largest part of the graduates work in the library het of the Ministry of Culture. This fact has determined the type of training the specialist at the Chair. The statistical facts of the determination this year show us the movement of the young specialists from one librarynet to another one. The main reason of such movement is the disparity of the type of training with the determination of the young specialists. Since 1968 the Chair has been training the specialists for different librarynets (kindergartens, schoollibraries, public libraries, technical libraries). But to this day the specialists for the scientifical libraries are not trained at the University, while the work at this type of the libraries has its own specific character. Since its foundation the Library and Scientific Information Chair solved many important problems during twenty years of its existence. Now the chair meets the following problems: the studying of library needs of our republic and finding out the type of training students according to them, the improving of conditions for the librarians, the rational determination of the Chair depends on successful solving this problems.